SALT CONTENT AND COMPOSITION OF FISH FLOOR PROKSIMAT FROM SEVERAL TYPES OF TRASH FISH SALTED WHICH IS BOILED AND WITHOUT BOILED - Rudy Irawan; Bustari Hasan; Tjipto Leksono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was to evaluate the effect of boiling with different water volume fish ratio on salt contention and proximate composition of salted trash fish. Salted trash fish obtained from salted fish collectors were grouped into different species of fish.The trash fish was boiled for 15 minutes with ratio of water volume to fish ratio of 3: 1, 4: 1, 5: 1, and 6: 1. Fish then was made for fish meal and the trash fish was analyzed for salt, protein, fat, and NPN . The results showed the salt content of fish meal decreased with the greater volume of boiling water. Salt consentrat of fishmeal processed by boiling in the water and fish 3:1, 4:1, 5:1, and 6:1 reduced from 13,62% to 2,61%, 2,40%, 2,22%, 1,70% respectively. Protein,fat, NPN also decreased from 29,96%, 3,97%, 1,69% respectively before boiling to 19,81%, 2,20%, 0,53% respectively after boiling.Keywords: trash fish salted, boiled